Bone defects substitution in total knee replacement (literature review) - Tankut, Oleksii; Dudko, Oleksii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
The number of primary and revision total knee arthroplasties is continuously increasing. Presence of bone defects is one of the challenging issues for these surgeries that affects significantly treatment results and increases expenses. Objective: to analyze methods of preoperative and intraoperative diagnostics of knee joint articulating surfaces bone defects and existing classifications according to their advantages and disadvantages, to substantiate the treatment strategy for cases with various types of bone defects. Methods: articles from PubMed, EBSCO and Google Scholar data bases were used for scientific review. Results: the main negative factors affecting the stability of prosthesis components are the size and the shape of bone defect, presence or absence of cortical layer, quality of bone tissue, as well as implant design and correct choice of material and technique for filling of the defect. Evaluation of materials of natural origin — different types of bone grafts and artificial augments made of metals and polymeric materials was performed. Methods of bone grafts preparation and their fixation are important for different types of bone defects. In more complicated cases individual guides and resection blocks, virtual prototyping technologies and 3D-printing should be used for individual manufacturing of endoprosthesis. Conclusions: Usage of modern materials and techniques for filling of bone defects in total knee arthroplasties requires precise preoperative planing and choice of proper technique. Structural or morselized bone allografts, bone cement alone or in combination with screws and meshes, metal or polymeric augments of various shapes should be used for small bone defects, depending from their type, but large bone defects require stems and individually produced oncological and hinge implants.